2014
DOI: 10.7860/jcdr/2014/8498.4821
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Splenic Artery Aneurysms: A Rare Cause of Extrahepatic Portal Hypertension and Massive Splenomegaly

Abstract: A 39-year-old female presented with one year history of dragging abdominal discomfort and fatigability of six months duration. She was non-alcoholic and had no other medical illness. General physical examination was unremarkable and abdominal palpation suggested splenomegaly of 10 cms below left coastal margin, which was firm and nontender. There was no ascites or hepatomegaly. Examination of other systems was unremarkable.Investigations revealed normal complete blood counts, urine analysis, liver and renal fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…In adult with cirrhosis, its incidence is reported between 7 % and 17 % [6,9]. It has been reported that SAA are more frequent in females compared to males [9,13,14] and adults compared to children in liver transplant patients [9]. We did not identify any literature that comprehensively evaluated the predictive factor for development of SAA in cirrhosis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In adult with cirrhosis, its incidence is reported between 7 % and 17 % [6,9]. It has been reported that SAA are more frequent in females compared to males [9,13,14] and adults compared to children in liver transplant patients [9]. We did not identify any literature that comprehensively evaluated the predictive factor for development of SAA in cirrhosis.…”
Section: Discussionmentioning
confidence: 91%
“…The pathogenesis of SAA is unknown. Pregnancy, degenerative atherosclerosis, portal hypertension, medial fibrodysplasia, arteritis, collagen vascular disease, alfa-1 antitrypsin deficiency, and pancreatitis are associated with increased incidence of SAA [9,13,15,16]. Several authors reported an increased elastase content of the aneurysm, with a subsequent decrease in the elastin content of the vessel wall.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It shows a 4:1 female preponderance, especially affecting the young reproductive age group. 5 , 6 , 10 The common causes of SAA include pregnancy, cirrhotic portal hypertension, trauma, and polyarteritis nodosa. 6 , 10 Fibromuscular dysplasia is a very rare cause of SAA.…”
Section: Discussionmentioning
confidence: 99%
“… 4 6 Splenic artery aneurysm can cause compression of the splenic veins, thus causing venous stasis and thrombosis. 5 , 6 This can lead to extrahepatic portal vein obstruction with consequent portosystemic shunting and enlarged collaterals. Our case showed a slowed portal flow, multiple enlarged lienorenal collaterals, and portal cavernoma, thus confirming EPHT.…”
Section: Discussionmentioning
confidence: 99%